PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA SEKOLAH DASAR (Studi Eksperimen Kelas IV SD Negeri 006 Terpadu Kubang Jaya) - Rika Delfita; Eddy Noviana; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low of student’s achievements on the subject of natural sciences. Therefore, it is necessary to study learning by Learning Cycle model. This learning model is a student-centered teaching. So that students can master the competencies that must be achieved in learning with the active role, so that students are able to reveal prior knowledge and the opportunity to refute, debate their ideas. This is a good approach to learning science. The main objective of this study was to examine the learning outcome of students who obtain the IPA between learning through Learning Cycle model with students who received conventional learning. This research was conducted in SDN 006 Integrated Kubang Jaya grade students IVC as the control class and the class IVA as an experimental class using Rondomized Pretest-Posttest control Group. Data were analyzed using the Wilcoxon Signed Rank Test with significance level α = 0.05. The results of the data analysis, in the experimental class earned an average of initial tests 63.12 into 75.05 on the average score of the final test. While the control group gained an average of initial tests of 62.74 and increased to 72.94 on the average of the final test. The results of this study indicate that there are differences in the average at the beginning of the test and the final test, but there was no difference statistically significant increase in learning outcomes among students who obtain IPA learning through Learning Cycle model, of the students who received conventional learning.Keywords : Learning Model Learning Cycle , Student’s Achievement Natural Sciences